Sosio-demografi dan Kepuasan Pengguna Podcast di Indonesia - Jenica Elisabeth Rotua Panjaitan (Jurnal Spektrum Komunikasi, 2021)
Podcasts is an audio-based information medium that is in demand by various countries, including in Indonesia, podcast enthusiasts have experienced a significant increase. This study looks at the socio-demographic factors and adaptation of podcast users through surveys and interviews which illustrate that the majority of podcast users in Indonesia are in big cities like Jakarta and come from diverse groups with expectations of getting entertainment where podcast users claim to be satisfied with the convenience and impact. which is obtained from the use of podcasts. Keywords: Podcasts, socio-demographics, satisfaction.